Epidemiology of Traumatic Peripheral Vascular Injury in Patients Presenting at Tertiary Care Center of Nepal - Lamichhane, Suman; Parajuli, Bikash; Rana, Kush Bahadur; Bhatta, Keshav; Kandel, Rajan; Lamichhane, Sandesh; Pandit, Sampada (Nepal Orthopaedic Association Journal, 2023)
Introduction: Traumatic peripheral vascular injury remains a significant cause of morbidity and mortality among the general population. Majority of peripheral arterial injury are caused by a blunt trauma with a concomitant soft tissue injury and fractures requiring multidisciplinary approach. Despite major efforts in establishing protocols and guidelines, optimal strategies of traumatic peripheral vascular injury are still under investigation and may vary depending upon the local setup and expertise available. The aim of this study was to identify the epidemiological profile of traumatic peripheral vascular injury presenting at tertiary care center of Nepal.Method: This is a retrospective study of patients who underwent vascular surgery in College of Medical Sciences Bharatpur, from December 2018 and July 2021. Ethical approval was taken from the Institutional Review Committee of College of Medical Sciences (Registration Number 2020-081). Data for the study was retrieved from Emergency records, operation records and medical record department of the hospital. A total of 63 cases of all age and sex were included in the study. Only patients having traumatic peripheral arterial injury and undergoing surgical intervention were included in the study. Patient data was initially tabulated using Microsoft Excel and analysis was done in SPSS software version 22.0.Result: Traumatic peripheral arterial injury was most commonly seen in 21-30 years (36.5%) age group with male preponderance (88.9%). Sharp injury mechanism accounted for (42.9%), followed by road traffic accidents (41.3%). Upper limb arterial injury was seen in 61.9% of patients and radial artery was the most common to be injured (34.9%). Associated tendon injury was seen in 63.5%, whereas nerve injury was seen in 20.6%. Complications were seen in 47.6% patients and wound infection was the most common ailment (12.7%).Conclusion: Traumatic peripheral vascular injury has a male preponderance with road traffic incidents being the major mechanism of injury in Nepal. These injuries have a high rate of complications.